High-Resolution Metagenomics of Human Gut Microbiota Generated by Nanopore and Illumina Hybrid Metagenome Assembly - Ye, Lianwei; Dong, Ning; Xiong, Wenguang; Li, Jun; Li, Runsheng; Heng, Heng; Chan, Edward Wai Chi; Chen, Sheng (Frontiers in Microbiology, 2022)
Metagenome assembly is a core yet methodologically challenging step for taxonomic classification and functional annotation of a microbiome. This study aims to generate the high resolution human gut metagenome using both Illumina and Nanopore platforms. Assembly was achieved using four assemblers, including Flye(nanopore), metaSPAdes (Illumina), hybridSPAdes (Illumina and nanopore) and OPERA-MS (Illumina and nanopore). Hybrid metagenome assembly was shown to generate contigs with almost same sizes comparable to those produced using Illumina reads alone, but were more contiguous, informative, and longer when compared to those assembled with Illumina reads only. In addition, hybrid metagenome assembly enables us to obtain complete plasmid sequences and much more AMR gene-encoding contigs than the Illumina method. Most importantly, using our workflow, 58 novel high quality metagenome bins were obtained from four assembly algorithms, in particular hybrid assembly (47/58), although metaSPAdes could provide 11 high quality bins independently. Among them, 29 bins were currently uncultured bacterial MAGs. These findings were highly consistent and supported by mock community data tested. In the analysis of BGCs, the number of BGCs in the contigs from hybridSPAdes (241) is higher than that of contigs from metaSPAdes (233). In conclusion, hybrid metagenome assembly could significantly enhance the efficiency of contig assembly, taxonomic binning and genome construction when compared with procedures using Illumina short-read data alone, indicating that nanopore long reads are highly useful in metagenomic applications. This technique could be used to create high-resolution references for future human metagenome studies.